New streptophenazines from marine Streptomyces sp. 182SMLY. Issue 4 (16th February 2017) - Liang, Ying; Chen, Lu; Ye, Xuewei; Anjum, Komal; Lian, Xiao-Yuan; Zhang, Zhizhen
Abstract: Six phenazines including three new ones were isolated from the culture of a marine actinomycete Streptomyces sp. 182SMLY. Based on the analyses of NMR, HRESIMS, optical rotation value, and CD data, the structures of these isolated compounds were determined as new phenazines of (-)-streptophenazines M–O and known phenazines of 1-carbomethoxyphenazine and (-)-streptophenazines A and B. (-)-Streptophenazine B showed activity in suppressing the growth of methicillin-resistant Staphylococcus aureus with MIC value of 4.2 μg/mL. Abstract :